Mucus extravasation and retention phenomena: a 24-year study - Almeida Janete D; Cabral Luiz; Balducci Ivan; Zerbinatti Daniel CZ; Hayashida Alethea M (BMC, 2010)
Abstract Background Mucoceles are benign lesions related to the minor salivary glands and their respective ducts frequently affecting oral structures which are generally asymptomatic. Mucoceles are generally characterized by swollen nodular lesions preferentially located on the lower lip and differ from the so-called ranulas, which are lesions located on the floor of the mouth and related to the sublingual or submandibular glands. Methods The objective of the present study was to analyze data such as age, gender, race and site of the lesion of 173 mucocele cases diagnosed at the Discipline of Stomatology, São José dos Campos Dental School, UNESP, over a period of 24 years (April 1980 to February 2003). Results Of the 173 cases analyzed, 104 (60.12%) were females and 69 (39.88%) were males. Age ranged from 4 to 70 years (mean ± SD: 17 ± 9.53) and most patients were in the second decade of life (n = 86, 49.42%); white (n = 124, 71.68%). The lower lip was the site most frequently affected by the lesions (n = 135, 78.03%), whereas the lowest prevalence was observed for the soft palate, buccal mucosa, and lingual frenum. Conclusion In this study, mucoceles predominated in white female subjects in the second decade of life, with the lower lip being the most frequently affected site.